Public Service Innovation Through Dukcapil Services Go Digital By Disdukcapil Probolinggo Regency - Vira Nur Wahyuni; Verto Septiandika (FISIP Universitas Malikussaleh, 2022)
Currently, innovation occupies a very strategic position in the public sector. This success attracts the public sector to continue to develop various types of innovations to improve public services. The development of the public sector shows that innovation cannot be separated from the rapid progress in technology, information and communication, so the term innovation is closely related to the term e-government. In order to realize a higher quality public service, the Disdukcapil of Probolinggo Regency released a new service in the field of population administration through an online service called Dukcapil Go Digital. This Go Digital Dukcapil is one of the ways taken by the Probolinggo Regency Disdukcapil to make it easier for the community to obtain administrative needs. The type of research used by the author is a qualitative approach with data collection in the form of a literature study with the aim of knowing more about the innovations implemented by the Disdukcapil Probolinggo Regency. The results showed that the innovations released and implemented by the Disdukcapil Probolinggo Regency were innovations that really helped the community to get services and population administration needs that were effective, efficient, fast and safe. This innovation is also expected to provide significant changes to population administration services at the Population and Civil Registry Office of Probolinggo Regency.Saat ini inovasi menempati posisi yang sangat strategis di sektor publik. Keberhasilan ini menarik sektor publik untuk terus mengembangkan beragam jenis inovasi untuk meningkatkan pelayanan publik. Perkembangan sektor publik menunjukkan bahwa inovasi tidak dapat dipisahkan dari kepesatan kemajuan di bidang teknologi, informasi dan komunikasi, sehingga istilah inovasi erat hubungannya dengan istilah e-government. Dalam rangka mewujudkan pelayanan publik yang lebih berkualitas, Disdukcapil Kabupaten Probolinggo merilis pelayanan baru di bidang administrasi kependudukan melalui layanan online bernama Dukcapil Go Digital. Dukcapil Go Digital ini merupakan salah satu cara yang diambil oleh Disdukcapil Kabupaten Probolinggo guna mempermudah masyarakat dalam memperoleh kebutuhan administrasi. Jenis penelitian yang digunakan penulis adalah pendekatan kualitatif dengan pengumpulan data berupa studi pustaka dengan tujuan untuk mengetahui lebih dalam mengenai inovasi yang diterapkan oleh Disdukcapil Kabupaten Probolinggo. Hasil penelitian menunjukkan bahwa inovasi yang dirilis dan diterapkan oleh Disdukcapil Kabupaten Probolinggo merupakan inovasi yang sangat membantu masyarakat untuk mendapat pelayanan dan kebutuhan administrasi kependudukan yang efektif, efisien, cepat dan aman. Dengan adanya inovasi ini juga diharapkan memberikan perubahan yang signifikan terhadap pelayanan administrasi kependudukan di Dinas Kependudukan dan Catatan Sipil Kabupaten Probolinggo.